Income Generation Opportunities through Secondary Agriculture towards Sustainability in Angul District of Odisha: A Case Study - , Gyanaranjan Sahoo, Ipsita Mishra, Monalisa Behera, Debasis Mishra (Archives of Current Research International, 2024)
Aims: The aim of the study was for attempting various Income Generation interventions to address poverty, unemployment and lack of economic opportunities which could increase participants’ ability towards secured livelihoods. Secondary agriculture is essentially a way of business development that aids in providing farming households in rural areas with income and employment. Place and Duration of the Study: The study was conducted in Krishi Vigyan Kendra Angul, Odisha between 2016-17 to 2021-22. Methodology: PRA survey of the village followed by group discussions and other approaches were conducted to identify the constraints and accordingly the process planning was performed for strengthening their livelihood. By the technological interventions from Krishi Vigyan Kendra, Angul the famers took trainings for grasping ideas & scientific knowledge about the enterprises. Periodically some critical inputs under various programme were also provided from the KVK. Results: As a result, year after year the farmers practicing bee-keeping could able to earn in an average of Rs. 5,14,100/- from 180 bee boxes by selling pure honey & bee-colonies. Besides this, another group of farmers with improved colour poultry breeds under backyard condition with an average yield of 1.62 kg could earn an average net return of Rs. 14,742/-. Conclusion: Given that the world's population is quickly growing, it is imperative for global agriculture to turn to secondary agriculture (honey bee and poultry farming) in order to provide opportunities not only for improving livelihood but also for nutritional security.